Power Requirements for Battery Maintenance and Temperature Profile on High Altitude Platform - Pirada Techavijit; Polkit Sukchalerm; Natthapong Wongphuangfuthaworn; Jakkrit Iamsawat (My University, 2024)
Experiments on high-altitude platform (HAP) at the nearspace must be faced with extremely low temperatures, reaching as low as -50 degrees Celsius, which exceeds the operational range of electronic systems. Especially, the battery that requires a heating system and thermal insulation. This paper will report temperature profile on the HAP flight and the results of experiments with the installation of the heating system to determine its adequacy, and measuring the electrical power needed for heating.
Keywords: Advanced Battery Technologies Research; Electric and Hybrid Vehicle Technologies; Engineering Applied Research